Encephalomyeloneuritis and arthritis after treatment with immune checkpoint inhibitors. Issue 4 (July 2020) - Nowosielski, Martha; Di Pauli, Franziska; Iglseder, Sarah; Wagner, Michaela; Hoellweger, Nicole; Nguyen, Van Anh; Gruber, Johann; Stockhammer, Günther
Abstract : Objective: Immunotherapy revolutionized melanoma treatment; however, immune-related adverse events, especially neurotoxicity, may be severe and require early and correct diagnosis as well as early treatment commencement. Methods: We report an unusual severe multiorgan manifestation of neurotoxicity after treatment with the anti-PDL1 immune checkpoint inhibitor, nivolumab, and the anticytotoxic T-lymphocyte-associated antigen 4 immune checkpoint inhibitor, ipilimumab, in a 47-year-old male patient with metastatic melanoma. Results: The patient developed immune-mediated synovitis and cranial neuritis, followed by longitudinal transverse myelitis, encephalitis, and optic neuritis. Early treatment with high-dose steroids and maintenance therapy with rituximab resulted in a favorable neurologic outcome. Conclusions: The frequency of spinal cord involvement and neuronal toxicity after cancer immunotherapy is very low and requires an extensive diagnostic workup to differentiate between disease progression and side effects. Immune checkpoint inhibitors should be discontinued and treatment with corticosteroids should be initiated early as the drug of first choice. Therapy may be escalated by other immune-modulating treatments, such as rituximab.